Descending the Reconstruction Ladder: Single-Stage Full-Thickness Skin Grafting for Wide Nasal Skin Malignant Defects - Villegas-Alzate, Francisco J.; Cabezas-Charry, Ana G.; Cardona, Víctor A.; Ayala, Juan F.; Villegas, José D. (Indian Journal of Plastic Surgery, 2025)
Complex nasal reconstructions traditionally use staged flaps, with skin grafts reserved for smaller defects.This study evaluates single-stage full-thickness skin grafting (FTSG) for wide nasal defects postcancer resection.A retrospective analysis included 52 patients with nasal malignant lesions limited to the skin, reconstructed in a single stage immediately after cancer resections. Defects were intentionally over- or downsized to align with the esthetic unit concept. Templates of the defects were used to harvest FTSG. All donor areas were closed primarily. The graft was carefully sutured to fit the defect, and bolsters were applied for 5 to 12 days. Postoperative taping was used for 4 months. Postoperative photographs were assessed by 92 independent raters using a visual analog scale evaluating five parameters: skin color matching, surface regularity, symmetry, perimetral contours, and overall nasal appearance. Results and complications were analyzed for statistical associations.On average, 3.5 of 9 nasal units per patient were reconstructed, covering 55.5% of the nasal surface. Local anesthesia was used in 90.4% of cases. Periclavicular and retroauricular donor sites were used in 61.5 and 34.6% of cases, respectively. Evaluators rated the outcomes at an average of 7.1/10 (range 5.1–8.8). The complication rate was 15.4%. No significant correlations were found between the outcomes and the analyzed factors.FTSG effectively reconstructs wide nasal defects in a single stage, predominantly under local anesthesia, with satisfactory outcomes. This approach signifies a descent down the reconstruction ladder, shifting from complex, flap-staged methods to a single-stage solution.
Keywords: nose; skin; questionnaires; patient-reported outcome